Health Psychology Perspectives on Stress and Coping Strategies Among Cancer Survivors - Lestari Putri; Andika Rahman (Magenta Journal De Healthymedi, 2025)
This study explores stress experiences and coping strategies among cancer survivors from a health psychology perspective. Using a qualitative phenomenological approach, data were collected through in-depth interviews with 25 cancer survivors recruited from oncology outpatient clinics and cancer support groups. The findings reveal that survivorship is characterized by persistent emotional stress, including fear of recurrence, anxiety, social isolation, and uncertainty regarding future health. To manage these challenges, survivors employed three interconnected coping mechanisms: problem-focused coping, emotion-focused coping, and meaning-focused coping. Problem-focused coping enhanced perceived control through treatment management and lifestyle adjustments, while emotion-focused coping facilitated emotional regulation through mindfulness, social support, and spirituality. Meaning-focused coping promoted resilience, gratitude, identity reconstruction, and personal growth. The findings contribute to health psychology literature and provide practical implications for developing comprehensive survivorship interventions that support long-term psychological well-being and quality of life.